2022
DOI: 10.3389/fsufs.2022.942645
|View full text |Cite
|
Sign up to set email alerts
|

Soil-biodegradable mulch is an alternative to non-biodegradable plastic mulches in a strawberry-lettuce double-cropping system

Abstract: Double-cropping strawberry (Fragaria × ananassa Duch.) and lettuce (Lactuca sativa L.) could be a sustainable alternative practice for diversified specialty crop growers. Plastic mulch is beneficial for strawberry and lettuce production with soil-biodegradable mulch (BDM) providing opportunities to reduce plastic waste generation and costs of mulch disposal. The objective of this study was to compare non-biodegradable plastic mulches and BDM to bare ground cultivation in a strawberry–lettuce double-cropping sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
(68 reference statements)
1
1
0
Order By: Relevance
“…Strawberry plant canopy percentage was at peak in PE mulch, followed by 6%PH, 2PH, 6%GG, 2%GG, and NP hydromulch. These results align with the prior study by Wang et al (2022), which indicated that PE mulch provided optimal strawberry crop canopy percentage compared to biodegradable plastic mulch and paper mulch. One might anticipate a similar pattern for strawberry crop canopy and leaf dry biomass across mulch treatments, but the present study revealed different outcomes from expectations.…”
Section: Strawberry Growth and Yield Protectionsupporting
confidence: 91%
“…Strawberry plant canopy percentage was at peak in PE mulch, followed by 6%PH, 2PH, 6%GG, 2%GG, and NP hydromulch. These results align with the prior study by Wang et al (2022), which indicated that PE mulch provided optimal strawberry crop canopy percentage compared to biodegradable plastic mulch and paper mulch. One might anticipate a similar pattern for strawberry crop canopy and leaf dry biomass across mulch treatments, but the present study revealed different outcomes from expectations.…”
Section: Strawberry Growth and Yield Protectionsupporting
confidence: 91%
“…New, unweathered PE, weedmat, and embossed BDM mulches included in this study ( Table 1 ) were the same products that had been used in a previous mulch experiment [ 41 ]. Surface microtopographic features of mulch samples were assessed using a digital microscope (Keyence VHX-7000) in the Composite Materials and Engineering Center at Washington State University (WSU) in Pullman, Washington, USA.…”
Section: Methodsmentioning
confidence: 99%